Case report: Autoimmune encephalomyelitis following cytomegalovirus infection after allogeneic hematopoietic stem cell transplantation - Yang, Min; Cai, Yu; Wan, Liping; Ji, Linhua; Song, Xian M. (Frontiers in Medicine, 2024)
Introduction Cytomegalovirus (CMV) can cause various end-organ diseases in immunocompromised hosts, including allogeneic hematopoietic cell transplant (allo-HSCT) recipients. Interestingly, CMV viremia has been associated with various complications and poor prognosis in allo-HSCT recipients. Complications involving the central nervous system (CNS) occur in 9–14% of patients following allo-HSCT. However, autoimmune encephalitis (AE) secondary to CMV infection after allo-HSCT has rarely been reported. Here we report a case of possible AE following CMV viremia after allo-HSCT, which was successfully treated with high-dose pulsed methylprednisolone and intravenous immunoglobulins (IVIg). Case description A 53-year-old female underwent allo-HSCT for T-lymphoblastic lymphoma/leukemia. The patient developed CMV viremia on day 36 after transplantation, and serum CMV-DNA remained positive after initiating ganciclovir antiviral therapy, turning negative one month later. Four months later, she started experiencing memory impairment, weakness in the left limbs, cognitive dysfunction, and hallucinations. A magnetic resonance imaging brain scan showed scattered ischemic lesions under the bilateral frontal cortex. Viral detection in cerebral spinal fluid (CSF) by next-generation gene sequencing technology showed no obvious abnormality. Antibodies specific to AE and paraneoplastic diseases in serum and CSF were absent. The oligoclonal bands in the CSF were detected using isoelectric focusing and immunofixation, and the results were negative. However, after extensive investigation regarding infections, autoimmune disorders, and recurrence of the malignancy, possible AE could not be excluded. The patient was treated with high-dose steroids combined with IVIg therapy; the patient’s symptoms were significantly improved. Conclusion The mechanisms of AE after allo-HSCT and the relationship with CMV infection should be further studied. Therefore, reporting this and similar cases will improve our awareness and understanding of the underlying disease mechanisms.